Deformation Analysis Derived by Magnitude of 6 of The 2017 Mentawai Earthquake based on GPS Data - Dwinida - nim 15114097, Yasya
Mentawai Islands are islands located west of Sumatra Island and close to subduction zones. Areas around the subduction zone have active seismic activity. This causes earthquakes to occur frequently in the Mentawai Islands that can trigger another disasters such as tsunamis. The earthquake that occurred in Mentawai Islands on 1 September 2017, caused changes in earth displacement, velocity, and strain. The technology that can be used for deformation studies is GPS. GPS observations are carried out by conducting continuous observations at several points of GPS observation stations around the Mentawai Islands and Sumatra Island. Obtained GPS monitoring data then processed using GAMIT / GLOBK devices to see the daily coordinates. After get the daily coordinates, calculate observation station displacement, velocity, and strain. All calculation results are then visualized using GMT software. Based on processing results, the average displacement is 1.95 mm. The largest displacement occurs at CPDG station of 4.37 mm. The smallest displacement occurs at TIKU station of 0.85 mm. The direction of velocity before and after the earthquake is headed to North East direction, that is be far from the earthquake epicenter. Both before and after the 1 September 2017 earthquake, strain conditions are still claimed by shortening. This is evident in the area of observation after the 1 September 2017 earthquake still occurs seismic activity in the energy accumulation (interseismic) phase.